La Política Pública Distrital de Ruralidad de Bogotá D.C. - Aguilar Galeano, Estíbaliz (Editorial Uniagustiniana, 2018)
The District's Public Policy (ppdr) was formulated for Bogotá City (Colombia) in 2006. It came up as an administration tool for the territorial sustainable environmental management and for overcoming the exclusion of the population, from a human development approach. We present here the process and results of a case study in which we intended to analyze the implementation of the ppdr to contribute to understand the obstacles, successes and new challenges occurred by the inclusion of human development in public environmental policies. The study focused on environmental issues reported by the District´s public entities, corresponding to the government periods 2008-2011 "Bogotá Positiva: Para Vivir Mejor" and 2012 - 2015 "Bogotá Humana". The analysis of the actions implemented under the ppdr framework showed that these have contributed in the betterment of human development in rural areas. It shows the importance of developing policies focused on the nature conservation as well as social and economic development of the populations living in direct contact with it, by integrating completely the equity issues into the environmental policies.